Issues of simulation, aggravation and dissimulation in expert questions for hearing disorders - O. A. Trunaeva; N. P. Onischenko (Инновационная медицина Кубани, 2019)
Those who are working in the conditions accompanied with industrial noise exceeding normal rates and who receive irreversible decrease in hearing of sensorineural nature, proceeding from the existing legislation, have to be exposed to expert assessment of the audiologist-otorhinolaryngologist, for the purpose of examination of professional suitability. Medical experts should face such phenomena as aggravation and simulation of hearing loss which exposure and also definition of a true threshold for sound perception, nature of the available violations, is their paramount task.The tests serving for simulation identification are carried out with application of subjective audiometry, i.e. with active participation of the examined person or by means of the objective audiometry excluding participation of the patient. Observation of the patient behavior, analysis of the anamnestic data, carrying out the acumetry and tuning testing, subjective and objective audiometry and also comparison of the obtained data allows to make expert assessment of a clinical case. The objective audiometry (OET, KSVP, ECOG, acoustic impedancemetry) is crucial in case of the doubts arising after carrying out a subjective audiometric research.